The Effectiveness of Spiritual Therapy in Improving Mental Peace in Schizophrenia Patients - Sri Ariyanti; Andi Arfah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Schizophrenia is a chronic mental disorder that causes disorganized thoughts, emotions, and behavior. Patients often experience anxiety, tension, and a loss of inner peace. Pharmacological therapy alone is often insufficient to restore mental balance. Spiritual therapy is a complementary approach that focuses on peace of mind, sincerity, and an enhanced relationship with God. Objective: This study aims to determine the effectiveness of spiritual therapy in increasing mental peace in schizophrenia patients. Method: The research design uses quasi experiment with a pretest-posttest design control group the design. The sample consisted of 40 schizophrenia patients divided into an intervention group (spiritual therapy) and a control group (routine care). Mental well-being was measured using the Spiritual Well-Being Scale. Scale (SWBS) before and after treatment. Data analysis using Paired t- test and Independent t- test. Results: The results showed a significant increase in mental well-being scores in the intervention group after receiving spiritual therapy (p = 0.001), while the control group showed no significant change (p = 0.243). Comparison between groups showed a significant difference (p = 0.002). Conclusion: Spiritual therapy is effective in increasing the mental peace of schizophrenia patients and can be used as a complementary therapy in psychiatric nursing care.